Adult Onset Still’s Disease: A Diagnostic Dilemma - Koirala, Dinesh; Pathak, UN; Adhikari, P; Shrestha, R; Neupane, C (Nepal Medical College Journal, 2021)
Adult-onset Still’s disease (ASD) is a rare clinical entity with unknown etiology, characterized by arthritis, fever, evanescent rash and other systemic presentations. This case report describes a 19-year-old male who presented with sore throat, fever, arthritis, evanescent rash, raised liver enzymes and hyperferritinemia. It also reveals the diagnostic dilemma faced during the diagnosis of the disease. He was diagnosed to have ASD based on Yamuguchi criteria after the exclusion of other potential diagnoses. Patient was treated with prednisolone and there was a good response with improvement in symptoms and laboratory indices.